2022
DOI: 10.3389/fcimb.2022.866452
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antiviral Activity of Potential Medicinal Plant Extracts Against Dengue and Chikungunya Viruses

Abstract: Dengue and chikungunya are two important mosquito-borne infections which are known to occur extensively in tropical and subtropical areas. Presently, there is no treatment for these viral diseases. In vitro antiviral screening of 25 extracts prepared from the plants of Vitex negundo, Plumeria alba, Ancistrocladus heyneanus, Bacopa monnieri, Anacardium occidentale, Cucurbita maxima, Simarouba glauca, and Embelia ribes using different solvents and four purified compounds (anacardic acid, chloroquinone, glaucarub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…The concentration at which the drugs showed ≥90% cell viability was used for evaluating the anti-CHIKV activity. The antiviral activity was assessed under different treatment settings (pre-treatment, co-treatment, and post-treatment) ( Alagarasu et al., 2022 ). Briefly, for pre-treatment, the cells were incubated with various concentrations of drugs for 24 h and the drugs were removed by washing and the cells were infected.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration at which the drugs showed ≥90% cell viability was used for evaluating the anti-CHIKV activity. The antiviral activity was assessed under different treatment settings (pre-treatment, co-treatment, and post-treatment) ( Alagarasu et al., 2022 ). Briefly, for pre-treatment, the cells were incubated with various concentrations of drugs for 24 h and the drugs were removed by washing and the cells were infected.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies using Chang liver cells and HepG2 cells exhibited safety of anacardic acid with IC 50 values 70.0 ± 3.0 µM, and 49.0 ± 8.0 µM respectively, which was much higher than the EC 50 value on E. protoscoleces (1.9 ± 2 µM), thus indicating the high safety margin of this compound [34]. We have recently reported excellent anti-dengue activity of Ananrcardic acid [35]. Studies with A. occidentale hexane leaf extract showed that the toxic effects occurred at higher doses compared to Cameroon folk medicine 12].…”
Section: Discussionmentioning
confidence: 88%
“…The cytotoxicity assay was performed using 3-(4,5-dimethythiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) to determine the effect of LFOB on Vero CCL-81 cells [ 42 ]. Briefly, a series of Vero cell monolayers were incubated with different concentrations of the LFOB (0 to 200 g/mL) for five days at 37 °C, followed by 3 h of incubation with MTT (5.0 mg/mL).…”
Section: Methodsmentioning
confidence: 99%